Children and Adolescents with Complex Regional Pain Syndrome: More Psychologically Distressed than Other Children in Pain?. (2013) - Logan, Deirdre E; Williams, Sara E; Carullo, Veronica P; Claar, Robyn Lewis; Bruehl, Stephen; Berde, Charles B
Abstract : BACKGROUND: Historically, in both adult and pediatric populations, a lack of knowledge regarding complex regional pain syndrome (CRPS) and absence of clear diagnostic criteria have contributed to the view that this is a primarily psychiatric condition. OBJECTIVE: To test the hypothesis that children with CRPS are more functionally disabled, have more pain and are more psychologically distressed than children with other pain conditions. METHODS: A total of 101 children evaluated in a tertiary care pediatric pain clinic who met the International Association for the Study of Pain consensus diagnostic criteria for CRPS participated in the present retrospective study. Comparison groups included 103 children with abdominal pain, 291 with headache and 119 with back pain. Children and parents completed self-report questionnaires assessing disability, somatization, pain coping, depression, anxiety and school attendance. RESULTS: Children with CRPS reported higher pain intensity and more recent onset of pain at the initial tertiary pain clinic evaluation compared with children with other chronic pain conditions. They reported greater functional disability and more somatic symptoms than children with headaches or back pain. Scores on measures of depression and anxiety were within normal limits and similar to those of children in other pain diagnostic groups. CONCLUSIONS: As a group, clinic-referred children with CRPS may be more functionally impaired and experience more somatic symptoms compared with children with other pain conditions. However, overall psychological functioning as assessed by self-report appears to be similar to that of children with other chronic pain diagnoses. Comprehensive assessment using a biopsychosocial framework is essential to understanding and appropriately treating children with symptoms of CRPS.